Factors affecting the visual outcomes and central macular thickness in diabetic maculopathy after intravitreal bevacizumab - Amna Rizwan; Asfandyar Asghar; Naila Yasmeen; Syed Ali Hasan Naqvi (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the outcomes of intravitreal bevacizumab in patients of diabetic maculopathy by anatomical outcomes and best-corrected visual acuity, and to assess the prognostic factors that influence the efficacy of intravitreal bevacizumab. Method: The quasi-experimental study was conducted at the Department of Ophthalmology, Fauji Foundation Hospital, Rawalpindi, Pakistan, from January 2019 to January 2020, and comprised patients with diabetic maculopathy who were administered intravitreal bevacizumab on a monthly basis for three months with further injections administered on an as-needed basis in cases of persistent macular oedema or deterioration of best-corrected visual acuity. The assessment was done pre-injection, and three and six months after the injection. Outcome variables were best-corrected visual acuity and central macular thickness. Data was analysed using SPSS 22. Results: Of the 34 patients, 2(5.9%) were males and 32(94.1%) were females. The overall mean age was 58±10 years. Of the 55 eyes, 27(49.1%) were right and 28(50.9%) were left eyes. After 3 months, the best-corrected visual acuity improved by one line in 20(36.4%) eyes. At 6 months, it improved by one line in 25(45.4%) eyes. After 3 months, the central macular thickness of 48(87.2%) eyes improved anatomically. At 6 months, a further decrease in central macular thickness resulted in 50(90.9%) eyes. The best-corrected visual acuity at 6 months was inversely correlated with central macular thickness and disruption of inner segment/outer segment integrity. Conclusion: Intravitreal bevacizumab injection led to appreciable improvement in best-corrected visual acuity and central macular thickness at 6 months. Disruption of inner segment/outer segment integrity, presence of exudates and cystic changes were noted that lead to poor visual prognosis. Key Words: Intravitreal injection, Bevacizumab, Prognostic factors, Diabetic retinopathy, Optical coherence tomography.